Impact of Comorbidities on Clinical Outcomes of Covid-19: A Case Study of the University of Ghana Medical Center (UGMC). - Otu-Anakwa, S. (University of Ghana, 2023)
Introduction: A new form of respiratory illness called COVID-19 arose in the last month of the year 2019 in China and has escalated globally, currently causing significant morbidity and mortality in the world. However, little is known about how this infection impact on the health of people with comorbidities. Objective: This study sought to assess the impact of comorbidities on clinical outcome of COVID 19 patients and to compare the clinical characteristics and outcome of COVID -19 patients with and without comorbidities. Methods: This was a single-centre retrospective cross sectional study making use of existing clinical data from the University of Ghana Medical Centre. A total of 325 patients’ data were used for this study. Bivariate analyses and multiple logistic regression analyses were conducted to determine the impact of pre-existing health conditions on the clinical outcome of COVID-19. Results: The prevalence of COVID-19 was 50%. Most of the factors analysed had no significant association to the outcome of the disease. Patients diagnosed with severe disease had a 70% reduced odd (AOR = 0.3; 95% CI = 0.0-0.3, p= 0.001) of surviving and a 90% reduced odd with those with critical illness (AOR = 0.1; 95% CI = 0.0-0.1, p<0.001) when associated to mild group. Conclusion: There was no significant impact of comorbidities on clinical outcome of COVID-19 patients. Patients with severe and critical illness are likely to die from the disease. This finding has a significant implication for public health with regard to healthcare delivery and future planning. Additional work should be carried out looking at the various peaks of the disease with larger populations to ascertain the impact of the disease amongst persons with underlying health conditions.
MPH.
Keywords: COVID-19; respiratory illness; China; University of Ghana Medical Centre (UGMC)